Quadcopter based emergency medikit delivery system for hill stations - C. R. Balamurugan; S. M. Revathy; P. Vijayakumar (Institute of Advanced Engineering and Science, 2020)
Nowadays UAV’s are more common for search, rescue and surveillance. A quadcopter UAV system is proposed to be used for aerial transportation of medicine. A Quadcopter has a drive chassis having a propeller, ESC, motor, frames and battery. The quadcopter is supported with GPS to know the exact position. To know the exact location and delivering medicine to accident area, an audio and video system is used. The quad frame built from quality materials, which are reinforced and much more stronger, this reduces arm breakage. A set of two plastic propellers, one normal and one pusher (reverse) to rotate and lift up the quadcopter. The brushless out-runner will provide more power with its high efficiency, long run times. The ESC includes programmable motor braking, soft start for helicopters and planes, timing, throttle input range and low-voltage cutoff. Lithium-Polymer (Li-Po) battery for very lightweight, small size and durability without losing charging capacity. The whole quadcopter process can be monitored and controlled by a remote control system, quadcopter will capture the live video and current status can be seen visualized and provides information about all the other exact conditions in real-time.